2023
DOI: 10.3390/jpm13091318
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Intracranial Pressure Sensor with Continuous Bluetooth Transmission via Mobile Application

Yasmeen Elsawaf,
Erik Jaklitsch,
Madison Belyea
et al.

Abstract: Hydrocephalus is a clinical disorder caused by excessive cerebrospinal fluid (CSF) buildup in the ventricles of the brain, often requiring permanent CSF diversion via an implanted shunt system. Such shunts are prone to failure over time; an ambulatory intracranial pressure (ICP) monitoring device may assist in the detection of shunt failure without an invasive diagnostic workup. Additionally, high resolution, noninvasive intracranial pressure monitoring will help in the study of diseases such as normal pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, the shortage of human resources in the MINSA (Peruvian Ministry of Health) is worsened in the poorest regions, where the lack of personnel prevents timely care [8]. This is why the use of low-cost technologies can contribute to In the review of the literature, studies have been found that focus on designing a low-cost and easyto-use electrocardiogram (ECG), focusing on capturing cardiac electrical signals, filtering noise, and transmitting them [9], adding in some cases Bluetooth technology to facilitate the early diagnosis of cardiac diseases [10]- [12] while other authors [13]- [15] present an approach on the design of a simulator of electrocardiographic signals, highlighting the reduction of cost by converting analog to digital signals. On the other hand, there have been significant advances in the monitoring and detection of cardiac arrhythmias [16], [17] through the development of a portable ECG device [18], data transmission through artificial intelligence while other research [19] presented a prototype based on machine learning for the detection and classification of arrhythmias in low-cost ECG devices with MATLAB and PSoC4 [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the shortage of human resources in the MINSA (Peruvian Ministry of Health) is worsened in the poorest regions, where the lack of personnel prevents timely care [8]. This is why the use of low-cost technologies can contribute to In the review of the literature, studies have been found that focus on designing a low-cost and easyto-use electrocardiogram (ECG), focusing on capturing cardiac electrical signals, filtering noise, and transmitting them [9], adding in some cases Bluetooth technology to facilitate the early diagnosis of cardiac diseases [10]- [12] while other authors [13]- [15] present an approach on the design of a simulator of electrocardiographic signals, highlighting the reduction of cost by converting analog to digital signals. On the other hand, there have been significant advances in the monitoring and detection of cardiac arrhythmias [16], [17] through the development of a portable ECG device [18], data transmission through artificial intelligence while other research [19] presented a prototype based on machine learning for the detection and classification of arrhythmias in low-cost ECG devices with MATLAB and PSoC4 [20], [21].…”
Section: Introductionmentioning
confidence: 99%